(untitled) (International Journal of Food and Nutritional Sciences, 2016)
The challenges of economic and social growth in emerging nations can be effectively addressed through industrialization. These nations’ phenomenal economic growth and improvement in living standards have coincided with the emergence of manufacturing. The socioeconomic growth of the nation has received a remarkable contribution from the SME sector. Poor capital base, technological accessibility, credit policy, inconsistent business services, high-quality human resources, low market awareness, and insufficient infrastructure are the problems that hinder the growth of this industry. In the current context of the globalization movement, the SME sectors are the economic development engine. The purpose of this essay is to evaluate several concerns in light of the economic situation in India. For the industrial expansion to be accelerated, entrepreneurship is essential. Small and medium-sized businesses are a powerful tool for fostering entrepreneurship. The issues of poverty, insecurity, unemployment, and overpopulation in the modern world can only be solved by this sector. This essay tried to emphasize the importance of SMEs in India’s economic growth. The contribution of SMEs to GDP growth is identified.